2006
DOI: 10.1007/s00068-005-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

The Ilizarov Ring External Fixator in Complex Open Fractures of the Tibia

Abstract: Introduction: Complex open fracture of the tibia particularly with bone defect and infection is one of the major problems in orthopedic surgery. There are many available alternatives in the management of these fractures. Aim: The purpose of this study is to evaluate the results and efficacy of the Ilizarov ring external fixator in treating complex open fractures of the tibia. Materials and Methods: We treated 25 patients with complex open fracture of the tibia using the Ilizarov ring external fixator between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…This study also showed that the hybrid external fixator has the ability of successful managing of the fracture, soft-tissue defect, infection, and bone loss simultaneously [19,20].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This study also showed that the hybrid external fixator has the ability of successful managing of the fracture, soft-tissue defect, infection, and bone loss simultaneously [19,20].…”
Section: Discussionmentioning
confidence: 55%
“…Although the classical Ilizarov method (ring external fixator) is an acceptable method for healing of docking site by continuous and gradual compression, as many other surgeons, we found that autogenous bone graft accelerates healing [19,21,22].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…6 Freshly, outer fixators like AO external fixator are utilized broadly as a part of creating nations however the rates of malunion and contamination are moderately high. 3,7 AO fixator is extremely prominent in treating sort 111A and B open fractures of the tibia in our set up due to it is effortlessly accessible ,practical, light weight, easy to apply, slightest awkward, giving insignificant agent injury, and great access to the soft tissue and monstrous contamination. It is especially helpful in sort 111A open breaks of tibia.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, external fixators like Ilizarov or AO external fixator are used extensively in developing countries but the rates of mal-union and infection are relatively high. 6 With AO external fixator, the efficacy of treatment in two studies were reported to be 20-31%. 7 Open fractures are classified into three major categories, depending on the mechanism of injury, soft tissue damage, and degree of skeletal involvement.…”
mentioning
confidence: 99%